A water-sulfur resistant monolithic catalyst and its preparation method and application
By combining titanium dioxide and lanthanum nitrate-silica sol composite in the catalyst, and using non-precious metal additives and aerosol spraying technology, the problem of poor stability of the catalyst in complex exhaust gas environments is solved, and efficient and stable catalytic performance and water and sulfur resistance are achieved.
Patent Information
- Application Number
- CN202411853994.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing catalysts have difficulty maintaining stable catalytic activity in complex exhaust gas environments, especially in the presence of high water vapor and sulfur oxides.
The protective layer of the integral catalyst is prepared by combining titanium dioxide and lanthanum nitrate-silica sol composite, and the non-precious metal additive components and aerosol spraying technology are used to optimize the component proportion and structure of the catalyst to improve its water and sulfur resistance.
It significantly improves the catalytic performance and stability of the catalyst, reduces the amount of precious metals, improves the resistance to water and sulfur, and ensures that the catalyst maintains high efficiency and activity in complex environments for a long time.
Smart Images

Figure CN119303572B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a water-sulfur resistant integral catalyst and a preparation method and application thereof. Background Art
[0002] Volatile organic compounds (VOCs) and carbon monoxide (CO) are common air pollutants. With the acceleration of industrialization and urbanization, the emissions of VOCs and CO continue to increase, causing serious harm to air quality and human health. In order to deal with the problem of air pollution, the state and local governments have formulated strict environmental protection laws and regulations, and put forward higher requirements for the emission limits of VOCs and CO. Enterprises need to take effective emission reduction measures to meet regulatory requirements. In practical applications, catalytic oxidation technology is currently one of the effective ways to remove CO and VOCs.
[0003] Traditional VOCs and CO catalysts are mainly divided into precious metal catalysts and non-precious metal catalysts. Precious metal catalysts usually use palladium (Pd), platinum (Pt), rhodium (Rh) and the like as active components. This type of catalyst has high catalytic activity. At lower temperatures, precious metal catalysts can effectively catalyze the oxidation of VOCs and CO. However, their cost is high. Under certain environmental conditions, precious metal catalysts may be deactivated by impurities. Non-precious metal catalysts have the advantage of low cost, but their catalytic activity and stability are still somewhat different from those of precious metal catalysts. In addition, the current traditional catalysts are not resistant enough to water vapor and SO2 in flue gas, and it is difficult to maintain stable catalytic activity in a complex exhaust gas environment. By regulating the precious metal components and auxiliary components and optimizing the preparation method, the catalytic performance and stability of the catalyst can be significantly improved and the preparation cost can be reduced. Summary of the invention
[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a water-sulfur resistant monolithic catalyst and a preparation method and application thereof.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] In a first aspect, the present invention provides a method for preparing a water-sulfur resistant monolithic catalyst, comprising the following steps:
[0007] S1: placing the carrier in the composite slurry, and calcining after impregnation to obtain a carrier with a protective coating;
[0008] S2: placing the carrier containing the protective coating obtained in step S1 in a solution of a non-precious metal additive compound, and calcining after impregnation to obtain a carrier containing a non-precious metal additive coating;
[0009] S3: spraying the Pd@SiO2 precursor sol on the surface of the carrier with the non-precious metal additive coating obtained in step S2, and then calcining to obtain a water-resistant sulfur-resistant monolithic catalyst.
[0010] Preferably, the composite slurry in step S1 comprises titanium dioxide and lanthanum nitrate-silica sol composite.
[0011] Preferably, after calcining lanthanum nitrate in step S2, La2O3 is obtained. The mass ratio of lanthanum nitrate to SiO2 in silica sol is 1-10 wt% based on La2O3, and the mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite is 5%.
[0012] Preferably, the mass concentration of titanium dioxide in the composite slurry in step S1 is 20%-30%, more preferably 25%.
[0013] Titanium dioxide has a large specific surface area and can carry and disperse active components. The protective layer of the TiO2-La2O3-SiO2 mixture formed after calcination prevents the subsequent active components from peeling off the carrier and blocking the pores, which may cause the catalyst to fail. At the same time, the addition of La effectively prevents the phase change of TiO2 and makes the protective layer more stable.
[0014] Preferably, the carrier in step S1 is a honeycomb carrier. More preferably, the carrier in step S1 is a 200-mesh cordierite honeycomb carrier.
[0015] The honeycomb carrier in the present invention can be used as the basic skeleton of the catalyst. Of course, other carriers with multi-porous structures in the prior art are also within the protection scope of the present invention.
[0016] Preferably, the non-precious metal additive compound solution in step S2 is an aqueous solution containing cerium nitrate, manganese nitrate, chromium nitrate and molybdenum nitrate. More preferably, the molar ratio of Ce, Mn, Cr and Mo in the non-precious metal nitrate solution is (0.4-1.6): (1-3): (0.5-1.5): (0.4-1.6), and further preferably 1:2:1:1.
[0017] Cerium (Ce) oxide in non-precious metal additive compounds contains abundant oxygen vacancies and has good ability to store and release oxygen. Manganese (Mn) has rich valence changes and can form a variety of oxides. These two components can provide abundant active oxygen species and regulate the properties of precious metals. Chromium (Cr) usually has high thermal stability and can maintain the activity of the catalyst at higher temperatures. At the same time, it can increase the surface acidity of the catalyst to avoid poisoning by sulfur species. The Mo=O bond in molybdenum (Mo) oxide can act as a sacrificial site to combine with sulfur species to form easily decomposable sulfites, effectively avoiding the deposition of sulfur species on the active components.
[0018] Preferably, in step S3, the Pd@SiO2 precursor aerosol is formed by passing a precursor solution through high-pressure nitrogen in an atomizer, and the precursor solution is a n-hexane solution containing a palladium salt, a surfactant, ammonia water, and a silicon source. The palladium salt is palladium nitrate and / or palladium chloride, the surfactant is polyethylene glycol monododecyl ether and / or polyethylene glycol mono-4-nonylphenyl ether, and the silicon source is tetraethoxysilane and / or methyltriethoxysilane.
[0019] More preferably, the content of palladium in the Pd@SiO2 precursor aerosol in step S3 is 0.1-1wt%.
[0020] Preferably, the molar ratio of Pd to Si in the Pd@SiO2 precursor slurry is 1:(80-160). More preferably, the molar ratio of Pd to Si in the Pd@SiO2 precursor slurry is 1:120.
[0021] As a common active component, precious metal Pd can decompose CO and VOCs at low temperatures, but it is easily inactivated by impurities. The present invention innovatively optimizes the ratio of non-precious metal and precious metal components to achieve the reduction of precious metal preparation; utilizes the characteristics of silicon source polycondensation to form a silica network structure, and wraps the palladium complex in the silica network to protect the Pd particles and avoid the influence of sulfur species; and uses aerosol spraying to prevent Pd particles from agglomerating.
[0022] Preferably, the step S3 specifically comprises: converting the precursor solution into an aerosol by atomization, carrying it into a storage tank by a carrier gas, pressurizing and heat-insulating it to keep it in an aerosol state, and spraying the carrier surface of the non-precious metal additive coating obtained in step S2 by a spray pen.
[0023] Preferably, the carrier gas is nitrogen with a flow rate of 100-300 mL / min.
[0024] Preferably, the spraying parameters of step S3 are: the spray pen pressure is 15-30 psi, and the spraying distance is 30-70 mm.
[0025] In a second aspect, the present invention also provides a water-resistant sulfur-resistant monolithic catalyst prepared by the above preparation method.
[0026] In a third aspect, the present invention also provides the use of the above-mentioned water-sulfur resistant integral catalyst in treating CO and / or VOCs.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) The present invention prepares an integral catalyst protective layer by combining titanium dioxide and lanthanum nitrate-silica sol composite. The protective layer of TiO2-La2O3-SiO2 mixture formed after calcination prevents the subsequent active components from peeling off from the carrier, blocking the pores and other problems that cause the catalyst to fail. At the same time, the addition of La effectively prevents the phase change of TiO2, making the protective layer more stable.
[0029] (2) The combination of cerium, molybdenum, manganese and chromium in the non-precious metal coating of the water- and sulfur-resistant monolithic catalyst of the present invention can retain and give full play to their respective functions, thereby improving the catalytic activity and the water- and sulfur-resistant properties of the catalyst. Controlling the ratio of the components of the non-precious metal coating and the ratio of the precious metal coating can minimize the use of precious metals, save costs and achieve the best catalytic effect. At the same time, the characteristics of the silicon source polycondensed to form a silica network structure are used to wrap the palladium complex in the silica network to resist the aggregation of precious metal particles and protect the precious metal active sites from the influence of sulfur species.
[0030] (3) The present invention utilizes an aerosol spraying device, such as Figure 1 As shown, the solution with active components is atomized to form an aerosol, which is carried into a storage tank by nitrogen, pressurized and kept warm to keep it in an aerosol state, and then the catalyst is sprayed with a spray pen. The aerosol spraying method can make the active components and the carrier closely combined, while ensuring the uniform dispersion of the active particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a schematic diagram of an aerosol spraying device;
[0032] Figure 2-Figure 5 This is a long-term test chart of the catalyst prepared in Example 1 of the present invention catalyzing CO, benzene, acetone and n-hexane in sequence.
[0033] Figure 1 In the figure: 1 is a sprayer, 2 is a constant temperature reactor, 3 is a valve, 4 is a storage tank, 5 is a heating belt, 6 is an air pump, 7 is an air outlet pipe, 8 is a spray pen, and 9 is a carrier. DETAILED DESCRIPTION
[0034] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0035] The present invention will be described in detail below with reference to the embodiments.
[0036] The aerosol spraying device used in the following examples and comparative examples is as follows: Figure 1As shown, it is composed of a constant temperature reactor 2, a storage tank 4, an air pump 6, and a spray pen 8. A sprayer 1 is arranged in the constant temperature reactor 2, the air pump 6 is connected to an air outlet pipe 7, the spray pen 8 is arranged at the end of the air outlet pipe 7 and is aligned with the air outlet of the air outlet pipe 7, the spray pen 8 is connected to the air pump 6, and the compressed air generated by the air pump 6 generates a high-speed airflow to spray the Pd@SiO2 precursor aerosol at the air outlet of the air outlet pipe 7 on the surface of the carrier 9. Nitrogen is introduced into the constant temperature reactor 2, a gas pipeline is connected between the constant temperature reactor 2 and the storage tank 4, and valves 3 are installed on the gas pipeline and the air outlet pipe. In addition, in order to reduce heat loss and keep the temperature and concentration of the aerosol stable, a heating belt 5 is arranged on the outer surface of the gas pipeline, the storage tank 4 and the air outlet pipe 7. The working parameters of this device during the working process are: the nitrogen inlet flow rate is 100-300 mL / min, the spray pen pressure is 15-30 psi, and the spraying distance is 30-70 mm.
[0037] Example 1
[0038] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0039] 1) Preparation of a carrier with a protective coating
[0040] Prepare slurry: add lanthanum nitrate to silica sol at a mass ratio of La2O3 / SiO2=5 wt%, control the mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite to be 5%, stir and dissolve, add titanium dioxide to the 5% lanthanum nitrate-silica sol composite, adjust the mass concentration of titanium dioxide to 25%, stir evenly, and obtain a composite slurry containing titanium dioxide.
[0041] Coating carrier: Place a 200 mesh honeycomb cordierite carrier (length*width*height=100mm*100mm*100mm) in a coating machine containing the above composite slurry.
[0042] Calcination: The coated cordierite carrier is taken out, placed in a calcination furnace, and calcined at a temperature of 550°C.
[0043] 2) Preparation of catalysts containing non-precious metal additive coatings
[0044] Prepare a non-precious metal compound solution: dissolve cerium nitrate, manganese nitrate, chromium nitrate and molybdenum nitrate in water to prepare a non-precious metal nitrate aqueous solution with a molar ratio of Ce:Mn:Cr:Mo=1:2:1:1, and maintain the mass concentration of the metal salt at 8%.
[0045] Impregnation of the support: The cordierite support containing the protective coating was placed in the above slurry for 10 min.
[0046] Drying and calcining: The impregnated carrier is dried and then placed in a calcining furnace and calcined at 550°C to obtain a carrier containing a non-precious metal additive coating.
[0047] 3) Preparation of water-resistant sulfur monolithic catalyst
[0048] Preparation of Pd@SiO2 precursor slurry: PdCl2 solution was quickly added to a hexane solution (960 mL) of polyethylene glycol monododecyl ether (40 g). Stirred at room temperature, and then 10 mL of 28 wt% ammonia solution was quickly added. After stirring for 2 h, tetraethoxysilane with a molar ratio of Pd:Si = 1:120 was added to the above solution mixture, and then stirred evenly at room temperature to maintain the mass fraction of palladium chloride in the slurry at 0.6%.
[0049] Aerosol spraying: Using an aerosol spraying device, such as Figure 1 As shown, the nitrogen inlet flow rate is set to 200 mL / min, the volume of the consumed aqueous solution is controlled to 80 mL, and the Pd@SiO2 precursor aerosol is sprayed on the carrier containing the non-precious metal additive coating using a spray pen at a pressure of 20 psi and a spraying distance of 50 mm.
[0050] Calcination: The sprayed carrier is placed in a calcination furnace and calcined at a temperature of 550°C to finally obtain a water-sulfur resistant monolithic catalyst.
[0051] 4) Catalysts for VOCs and CO catalytic oxidation and their anti-water and sulfur applications
[0052] The prepared catalyst was subjected to fixed bed reaction, CO gas concentration: 1.5%, benzene gas concentration: 1000 ppm, acetone gas concentration: 1000 ppm, n-hexane gas concentration: 1000 ppm, O2 concentration: 12 vol.%, water content: 15%, SO2 gas concentration: 10 ppm, N2: balance gas, gas space velocity: 18000 h -1 , reaction temperature: 100-400°C. Under this condition, the catalyst activity and resistance application tests were carried out.
[0053] Example 2
[0054] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0055] 1) Preparation of a carrier with a protective coating
[0056] Prepare slurry: add lanthanum nitrate to silica sol at a mass ratio of La2O3 / SiO2=3 wt%, control the mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite to 5%, stir and dissolve, add titanium dioxide to the 5% lanthanum nitrate-silica sol composite, adjust the mass concentration of titanium dioxide to 25%, stir evenly, and obtain a slurry containing titanium dioxide.
[0057] Coating the carrier: Place a 200 mesh honeycomb cordierite carrier in a coating machine containing the above slurry.
[0058] Calcination: The coated cordierite carrier is taken out, placed in a calcination furnace, and calcined at a temperature of 550°C.
[0059] 2) Preparation of catalysts containing non-precious metal additive components:
[0060] Prepare a non-precious metal solution: dissolve cerium nitrate, manganese nitrate, chromium nitrate and molybdenum nitrate in water to prepare a non-precious metal nitrate aqueous solution with a molar ratio of Ce:Mn:Cr:Mo=0.4:3:0.5:0.4, and maintain the mass concentration of the metal salt at 8%.
[0061] Impregnation of the support: The cordierite support containing the protective coating was placed in the above slurry for 10 min.
[0062] Drying and calcination: The impregnated support is dried and then placed in a calcination furnace and calcined at 550°C.
[0063] 3) Preparation of water-sulfur resistant monolithic catalyst:
[0064] Preparation of Pd@SiO2 precursor slurry: PdCl2 solution was quickly added to a hexane solution (960 mL) of polyethylene glycol monododecyl ether (40 g). Stirred at room temperature, then quickly added 10 mL of 28 wt% ammonia solution, stirred for 2 h, then added methyltriethoxysilane with a molar ratio of Pd:Si = 1:80 to the above solution mixture, and then stirred evenly at room temperature, keeping the mass fraction of palladium chloride in the slurry at 0.1%. The remaining steps were the same as step 3 of Example 1).
[0065] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0066] Example 3
[0067] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0068] 1) Preparation of a carrier with a protective coating
[0069] Prepare slurry: add lanthanum nitrate to silica sol at a mass ratio of La2O3 / SiO2=8 wt%, control the mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite to 5%, stir and dissolve, add titanium dioxide to the 5% lanthanum nitrate-silica sol composite mixture, adjust the mass concentration of titanium dioxide to 25%, stir evenly, and obtain a composite slurry containing titanium dioxide.
[0070] Coating the carrier: Place a 200 mesh honeycomb cordierite carrier in a coating machine containing the above slurry.
[0071] Calcination: The coated cordierite carrier is taken out, placed in a calcination furnace, and calcined at a temperature of 550°C.
[0072] 2) Preparation of catalysts containing non-precious metal additive components:
[0073] Prepare a non-precious metal solution: dissolve cerium nitrate, manganese nitrate, chromium nitrate and molybdenum nitrate in water to prepare a non-precious metal nitrate aqueous solution with a molar ratio of Ce:Mn:Cr:Mo=1.6:1:1.5:1.6, and maintain the mass concentration of the metal salt at 8%.
[0074] Impregnation of the support: The cordierite support containing the protective coating was placed in the above slurry for 10 min.
[0075] Drying and calcination: The impregnated support is dried and then placed in a calcination furnace and calcined at 550°C.
[0076] 3) Preparation of water-sulfur resistant monolithic catalyst:
[0077] Preparation of Pd@SiO2 precursor slurry: PdCl2 solution was quickly added to the n-hexane solution (960 mL) of polyethylene glycol mono-4-nonylphenyl ether (40 g). Stirred at room temperature, then quickly added 10 mL of 28 wt% ammonia solution, stirred for 2 h, and then added methyltriethoxysilane with a molar ratio of Pd:Si = 1:160 to the above solution mixture, and then stirred evenly at room temperature, keeping the mass fraction of palladium chloride in the slurry at 1%. The remaining steps are the same as step 3 of Example 1).
[0078] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0079] Example 4
[0080] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0081] 1) Preparation of a carrier containing a protective coating:
[0082] Prepare slurry: add lanthanum nitrate to silica sol at a mass ratio of La2O3 / SiO2=1 wt%, control the mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite to 5%, stir and dissolve, add titanium dioxide to the 5% lanthanum nitrate-silica sol composite mixture, adjust the mass concentration of titanium dioxide to 20%, stir evenly, and obtain a composite slurry containing titanium dioxide.
[0083] Coating the carrier: Place the cordierite carrier in the above slurry, ensure that the carrier is fully immersed in the slurry, and make the slurry evenly coated on the surface of the cordierite carrier.
[0084] Calcination: The coated cordierite carrier is taken out, placed in a calcination furnace, and calcined at a temperature of 550°C.
[0085] 2) Preparation of a catalyst containing a non-precious metal auxiliary component: Same as step 2) in Example 1.
[0086] 3) Preparation of water-sulfur resistant monolithic catalyst: same as step 3) in Example 1.
[0087] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0088] Example 5
[0089] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0090] 1) Preparation of a carrier containing a protective coating:
[0091] Prepare slurry: add lanthanum nitrate to silica sol at a mass ratio of La2O3 / SiO2=10 wt%, control the mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite to 5%, stir and dissolve, add titanium dioxide to the 5% lanthanum nitrate-silica sol composite mixture, adjust the mass concentration of titanium dioxide to 30%, stir evenly, and obtain a composite slurry containing titanium dioxide.
[0092] Coating the carrier: Place the cordierite carrier in the above slurry, ensure that the carrier is fully immersed in the slurry, and make the slurry evenly coated on the surface of the cordierite carrier.
[0093] Calcination: The coated cordierite carrier is taken out, placed in a calcination furnace, and calcined at a temperature of 550°C.
[0094] 2) Preparation of a catalyst containing a non-precious metal auxiliary component: Same as step 2) in Example 1.
[0095] 3) Preparation of water-sulfur resistant monolithic catalyst: same as step 3) in Example 1.
[0096] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0097] Example 6
[0098] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0099] 1) Prepare a carrier with a protective coating: same as step 1) in Example 1.
[0100] 2) Preparation of catalysts containing non-precious metal additive components:
[0101] Prepare a non-precious metal solution: dissolve cerium nitrate, manganese nitrate, chromium nitrate and molybdenum nitrate in water to prepare a non-precious metal nitrate aqueous solution with a molar ratio of Ce:Mn:Cr:Mo=1.2:2.5:1.2:1.2, and maintain the mass concentration of the metal salt at 8%.
[0102] Impregnation of the support: The cordierite support containing the protective coating was placed in the above slurry for 10 min.
[0103] Drying and calcination: The impregnated support is dried and then placed in a calcination furnace and calcined at 550°C.
[0104] 3) Preparation of water-sulfur resistant monolithic catalyst: same as step 3) in Example 1.
[0105] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0106] Example 7
[0107] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0108] 1) Prepare a carrier with a protective coating: same as step 1) in Example 1.
[0109] 2) Preparation of catalysts containing non-precious metal additive components:
[0110] Prepare a non-precious metal solution: dissolve cerium nitrate, manganese nitrate, chromium nitrate and molybdenum nitrate in water to prepare a non-precious metal nitrate aqueous solution with a molar ratio of Ce:Mn:Cr:Mo=0.8:1.5:0.8:0.8, and maintain the mass concentration of the metal salt at 8%.
[0111] Impregnation of the support: The cordierite support containing the protective coating was placed in the above slurry for 10 min.
[0112] Drying and calcination: The impregnated support is dried and then placed in a calcination furnace and calcined at 550°C.
[0113] 3) Preparation of water-sulfur resistant monolithic catalyst: same as step 3) in Example 1.
[0114] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0115] Example 8
[0116] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0117] 1) Prepare a carrier with a protective coating: same as step 1) in Example 1.
[0118] 2) Preparation of a catalyst containing a non-precious metal auxiliary component: Same as step 2) in Example 1.
[0119] 3) Preparation of water-sulfur resistant monolithic catalyst:
[0120] Preparation of Pd@SiO2 precursor slurry: Pd(NO3)2 solution was quickly added to the n-hexane solution (960 mL) of polyethylene glycol mono-4-nonylphenyl ether (40 g). Stirring was performed at room temperature, and then 10 mL of 28 wt% ammonia solution was quickly added. After stirring for 2 h, tetraethoxysilane with a molar ratio of Pd:Si=1:120 was added to the above solution mixture, and then stirred evenly at room temperature to maintain the mass fraction of palladium chloride in the slurry at 0.6%.
[0121] Aerosol spraying: The Pd@SiO2 precursor slurry is atomized to form an aerosol using an aerosol spraying device. The aerosol is brought into a storage tank by nitrogen and pressurized and kept in an aerosol state. The nitrogen inlet flow rate is set to 300 mL / min, the volume of the consumed aqueous solution is controlled to 80 mL, and the Pd@SiO2 precursor aerosol is sprayed on the catalyst containing the non-precious metal additive component using a spray pen at a pressure of 30 psi and a spray distance of 70 mm.
[0122] Calcination: The sprayed carrier is placed in a calcination furnace and calcined at 550°C to finally obtain a water-sulfur-resistant VOCs and CO integral catalyst.
[0123] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0124] Example 9
[0125] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0126] 1) Prepare a carrier with a protective coating: same as step 1) in Example 1.
[0127] 2) Preparation of a catalyst containing a non-precious metal auxiliary component: Same as step 2) in Example 1.
[0128] 3) Preparation of water-sulfur resistant monolithic catalyst:
[0129] Preparation of Pd@SiO2 precursor slurry: PdCl2 solution was quickly added to a hexane solution (960 mL) of polyethylene glycol monododecyl ether (40 g). Stirred at room temperature, and then 10 mL of 28 wt% ammonia solution was quickly added. After stirring for 2 h, tetraethoxysilane with a molar ratio of Pd:Si = 1:120 was added to the above solution mixture, and then stirred evenly at room temperature to maintain the mass fraction of palladium chloride in the slurry at 0.6%.
[0130] Aerosol spraying: The Pd@SiO2 precursor slurry is atomized to form an aerosol using an aerosol spraying device. The aerosol is brought into a storage tank by nitrogen and pressurized and kept in an aerosol state. The nitrogen inlet flow rate is set to 180 mL / min, the volume of the consumed aqueous solution is controlled to 80 mL, and the Pd@SiO2 precursor aerosol is sprayed on the catalyst containing the non-precious metal additive component using a spray pen at a pressure of 15 psi and a spraying distance of 30 mm.
[0131] Calcination: The sprayed carrier is placed in a calcination furnace and calcined at 550°C to finally obtain a water-sulfur-resistant VOCs and CO integral catalyst.
[0132] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0133] Comparative Example 1
[0134] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0135] There is no step 1 of Example 1).
[0136] Preparation of a catalyst containing a non-precious metal additive component: directly take a 200 mesh honeycomb cordierite carrier (length*width*height=100mm*100mm*100mm). Dissolve nitrate in water to prepare a solution using the same formula and proportion as in step 2) of Example 1, and calcine at 550°C using the same impregnation method as in Example 1.
[0137] Preparation of water-sulfur resistant VOCs and CO monolithic catalyst: Same as step 3 of Example 1).
[0138] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0139] Comparative Example 2
[0140] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0141] Preparation of a cordierite carrier with a protective coating: Mix titanium dioxide with 5% silica sol, wherein the mass concentration of titanium dioxide is adjusted to 25%, stir evenly to obtain a slurry containing titanium dioxide, coat it with a coating machine, and calcine at 550°C.
[0142] Preparation of a catalyst containing a non-precious metal promoter component: Same as step 2 of Example 1).
[0143] Preparation of water-resistant sulfur monolithic catalyst: same as step 3 of Example 1).
[0144] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0145] Comparative Example 3
[0146] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0147] Preparation of a cordierite carrier containing a protective coating: Same as step 1 of Example 1).
[0148] Preparation of a catalyst containing a non-precious metal promoter component: Same as step 2 of Example 1).
[0149] Preparation of water-sulfur resistant monolithic catalyst: The precious metal solution used is the same as the formula of step 3) of Example 1, and the cordierite carrier containing the non-precious metal additive is directly immersed in the Pd@SiO2 precursor solution, taken out and dried after 10 minutes, and calcined at 550°C.
[0150] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0151] Comparative Example 4
[0152] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0153] Preparation of a cordierite carrier containing a protective coating: Same as step 1 of Example 1).
[0154] Preparation of a catalyst containing a non-precious metal promoter component: Same as step 2 of Example 1).
[0155] Preparation of water-sulfur resistant monolithic catalyst: palladium chloride is dissolved in water to prepare a palladium chloride aqueous solution with a mass concentration of 0.6 wt%, an aerosol spray device is used to atomize the palladium chloride aqueous solution to form an aerosol, which is sprayed on a cordierite carrier containing a protective coating, and calcined at 550°C.
[0156] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0157] Comparative Example 5
[0158] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0159] Preparation of a cordierite carrier containing a protective coating: Same as step 1 of Example 1).
[0160] There is no step 2 of Example 1).
[0161] Preparation of water-sulfur resistant monolithic catalyst: Using the same spraying parameters as in step 3) of Example 1), the same Pd@SiO2 precursor solution as in step 3) of Example 1) was sprayed directly onto the cordierite support containing the protective coating and calcined at 550°C.
[0162] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0163] Comparative Example 6
[0164] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0165] Preparation of a cordierite carrier containing a protective coating: Same as step 1 of Example 1).
[0166] Preparation of a catalyst containing a non-precious metal auxiliary component: dissolving manganese nitrate in water to prepare a solution, impregnating the manganese nitrate on a cordierite carrier containing a protective coating using the same impregnation method as in Example 1, and calcining at 550°C.
[0167] Preparation of water-resistant sulfur monolithic catalyst: same as step 3 of Example 1).
[0168] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0169] Comparative Example 7
[0170] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0171] Preparation of a cordierite carrier containing a protective coating: Same as step 1 of Example 1).
[0172] Preparation of a catalyst containing a non-precious metal auxiliary component: dissolving molybdenum nitrate in water to prepare a solution, impregnating the molybdenum nitrate on a cordierite carrier containing a protective coating using the same impregnation method as in Example 1, and calcining at 550°C.
[0173] Preparation of water-resistant sulfur monolithic catalyst: same as step 3 of Example 1).
[0174] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0175] Comparative Example 8
[0176] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0177] Preparation of a cordierite carrier containing a protective coating: Same as step 1 of Example 1).
[0178] Preparation of a catalyst containing a non-precious metal auxiliary component: dissolving manganese nitrate and chromium nitrate in water to prepare a solution, impregnating manganese nitrate and chromium nitrate on a cordierite carrier containing a protective coating using the same impregnation method as in Example 1, and calcining at 550°C.
[0179] Preparation of water-resistant sulfur monolithic catalyst: same as step 3 of Example 1).
[0180] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0181] Comparative Example 9
[0182] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0183] Preparation of a cordierite carrier containing a protective coating: Same as step 1 of Example 1).
[0184] Preparation of a catalyst containing a non-precious metal auxiliary component: Dissolve manganese nitrate, chromium nitrate and molybdenum nitrate in water to prepare a solution, impregnate manganese nitrate, chromium nitrate and molybdenum nitrate on a cordierite carrier containing a protective coating using the same impregnation method as in Example 1, and calcine at 550°C.
[0185] Preparation of water-sulfur resistant VOCs and CO monolithic catalyst: Same as step 3 of Example 1).
[0186] Catalyst for catalytic oxidation of VOCs and CO and its water-sulfur resistance application: same as step 4 of Example 1).
[0187] Comparative Example 10
[0188] A water-sulfur resistant monolithic catalyst specifically comprises the following steps:
[0189] 1) Preparation of a carrier containing a protective coating:
[0190] Preparation of slurry: Add lanthanum nitrate to silica sol at a mass ratio of La2O3 / SiO2=5 wt%, control the mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite to be 5%, stir and dissolve, add titanium dioxide to the 5% lanthanum nitrate-silica sol composite, adjust the mass concentration of titanium dioxide to 10%, stir evenly, and obtain a composite slurry containing titanium dioxide.
[0191] Coating the carrier: Place the cordierite carrier in the above slurry, ensure that the carrier is fully immersed in the slurry, and make the slurry evenly coated on the surface of the cordierite carrier.
[0192] Calcination: The coated cordierite carrier is taken out, placed in a calcination furnace, and calcined at a temperature of 550°C.
[0193] 2) Preparation of a catalyst containing a non-precious metal auxiliary component: Same as step 2) in Example 1.
[0194] 3) Preparation of water-sulfur resistant monolithic catalyst: same as step 3) in Example 1.
[0195] 4) Catalyst for catalytic oxidation of VOCs and CO and its water and sulfur resistance application: same as step 4 of Example 1).
[0196] It should be noted that the comparative examples in this application are provided for comparison with the embodiments and are themselves also part of the embodiments.
[0197] Under this condition, the catalyst is used for catalytic oxidation. The catalytic ability of the catalyst is generally evaluated by the 99% conversion rate temperature. The test results for CO and VOCs are shown in Table 1.
[0198] Table 1 Test results of catalysts of examples and comparative examples for CO and VOCs
[0199]
[0200] The difference between Example 1 and Example 2-Example 5 and Comparative Example 1, Comparative Example 2, and Comparative Example 10 is mainly that the mass ratio of lanthanum nitrate / SiO2 in step 1) is different, and the mass concentration of titanium dioxide is different. The role of the protective coating in step 1) is to prevent the subsequent active components from peeling off from the carrier and blocking the pores, thereby causing the catalyst to fail. Comparative Example 1 does not have a protective coating, and the active components are easy to fall off during use, affecting the stability and life of the catalyst. At the same time, different concentrations of titanium dioxide will cause the thickness, porosity and other characteristics of the coating to change, thereby affecting the subsequent loading of active components and the overall performance of the catalyst. Comparative Example 2 does not have lanthanum nitrate, and the use of SiO2 sol alone cannot provide the same performance as lanthanum nitrate-SiO2 composite sol, but too low lanthanum nitrate (i.e., too low La2O3) is not suitable for protecting the crystalline phase of TiO2, and too high a concentration causes the coating to be too dense.
[0201] The difference between Example 1 and Example 6, Example 7 and Comparative Examples 5 to Comparative Examples 9: In step 2), the molar ratio of the aqueous solution of the non-precious metal nitrate additive is different. Comparative Example 5 lacks step 2), and the non-precious metal additive can combine with the precious metal active component to protect the precious metal and improve the water and sulfur resistance of the catalyst. The single or partial combination of non-precious metal additives in Comparative Examples 6 to Comparative Examples 9 may not be able to exert the best synergistic effect, resulting in catalyst performance that is inferior to that of Example 1. Combinations of cerium, manganese, chromium and molybdenum in different proportions will have different oxygen binding capacity and sulfur resistance. A reasonable ratio can give full play to the advantages of each element and improve catalyst performance.
[0202] The difference between Example 1 and Examples 8-9 and Comparative Examples 3-4: The loading method or aerosol spraying parameters in step 3) are different. Step 3) of Comparative Example 3 adopts an impregnation method instead of an aerosol spraying method, and step 3) of Comparative Example 4 adopts direct spraying of a palladium chloride solution. By comparison, it was found that the activity of the catalyst prepared by the impregnation method decreased, which may lead to uneven distribution of active components, easy loss of effective ingredients, and poor utilization of the slurry during the preparation process. Direct spraying of the palladium chloride solution causes Pd to be directly exposed to the surface and poisoned by sulfur species. Different parameters may lead to differences in the particle size of the active component, spraying density, etc., thereby affecting the number of active sites and catalytic performance of the catalyst.
[0203] Figure 2-Figure 5 This is a long-term test chart of the catalyst prepared in Example 1 of the present invention for CO, benzene, acetone, and n-hexane. The results show that the catalyst remains stable for 100 hours for CO, benzene, acetone, and n-hexane at a water content of 15% and the presence of 10 ppm SO2.
[0204] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a water-sulfur resistant monolithic catalyst, characterized in that: The preparation method of the catalyst comprises the following steps: S1: placing a carrier in a composite slurry, and calcining after impregnation to obtain a carrier containing a protective coating, wherein the composite slurry includes titanium dioxide and a lanthanum nitrate-silica sol composite; S2: placing the carrier containing the protective coating obtained in step S1 in a solution of a non-precious metal additive compound, and calcining after impregnation to obtain a carrier containing a non-precious metal additive coating; S3: spraying a Pd@SiO2 precursor aerosol onto the surface of the carrier of the non-precious metal additive coating obtained in step S2 and then calcining to obtain a water-resistant sulfur monolithic catalyst; The non-precious metal auxiliary compound solution in step S2 is a non-precious metal nitrate aqueous solution containing cerium nitrate, manganese nitrate, chromium nitrate and molybdenum nitrate, and the molar ratio of Ce, Mn, Cr and Mo in the non-precious metal nitrate aqueous solution is (0.4-1.6): (1-3): (0.5-1.5): (0.4-1.6).
2. The preparation method according to claim 1, characterized in that: The lanthanum nitrate in the lanthanum nitrate-silica sol composite of step S1 is calcined in step S2 to obtain La2O3. The mass ratio of lanthanum nitrate to SiO2 in silica sol is 1-10wt% based on La2O3. The mass percentage of the sum of lanthanum nitrate and SiO2 in the lanthanum nitrate-silica sol composite is 5%. The mass concentration of titanium dioxide in the composite slurry is 20%-30%.
3. The preparation method according to claim 1, characterized in that: The carrier in step S1 is a honeycomb carrier.
4. The preparation method according to claim 1, characterized in that: The Pd@SiO2 precursor aerosol in S3 is a Pd@SiO2 precursor slurry formed in an atomizer by a carrier gas. The Pd@SiO2 precursor slurry is a n-hexane solution containing a palladium salt, a surfactant, an ammonia solution, and a silicon source. The palladium salt is palladium nitrate and / or palladium chloride. The surfactant is polyethylene glycol monododecyl ether and / or polyethylene glycol mono-4-nonylphenyl ether. The silicon source is tetraethoxysilane and / or methyltriethoxysilane.
5. The preparation method according to claim 1, characterized in that: The content of palladium in the Pd@SiO2 precursor aerosol in step S3 is 0.1-1wt%.
6. The preparation method according to claim 4, characterized in that: The molar ratio of Pd to Si in the Pd@SiO2 precursor slurry is 1:(80-160).
7. The preparation method according to claim 1, characterized in that: In step S3, spraying is performed using a spray pen, the pressure of the spray pen is 15-30 psi, and the spraying distance is 30-70 mm.
8. A monolithic catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the monolithic catalyst according to claim 8 in treating CO and / or VOCs.
Citation Information
Patent Citations
Integrally-extruded honeycomb catalyst for selective catalytic reduction (SCR) smoke denitration and preparation process of catalyst
CN102886266A
Preparation method of composite metal oxide catalyst for catalytic decomposition for VOCs (Volatile Organic Compounds)
CN107442106A
Sulfur-resistant CO oxidation catalyst, preparation method and application
CN116251586A
Monolithic catalyst for removing CO and VOCs and preparation method thereof
CN117181217A